Confirmation that Xq27 and Xq28 are susceptibility loci for migraine in independent pedigrees and a case-control cohort - Maher, B. H.; Kerr, M.; Cox, H. C.; MacMillan, J. C.; Brimage, P. J.; Esposito, T.; Gianfrancesco, F.; Haupt, L. M.; Nyholt, D. R.; Lea, R. A.; Griffiths, L. R. (Neurogenetics, 2012)
Investigations into migraine genetics have suggested that susceptibility loci exist on the X chromosome. These reports are supported by evidence that demonstrates male probands as having a higher proportion of affected first-degree relatives as well as the female preponderance of 3:1 that the disorder displays. We have previously implicated the Xq24-28 locus in migraine using two independent multigenerational Australian pedigrees that demonstrated excess allele sharing at the Xq24, Xq27 and Xq28 loci. Here, we expand this work to investigate a further six independent migraine pedigrees using 11 microsatellite markers spanning the Xq27–28 region. Furthermore, 11 candidate genes are investigated in an Australian case-control cohort consisting of 500 cases and 500 controls. Microsatellite analysis showed evidence of excess allele sharing to the Xq27 marker DXS8043 (LOD* 1.38 P = 0.005) in MF879 whilst a second independent pedigree showed excess allele sharing to DXS8061 at Xq28 (LOD* 1.5 P = 0.004). Furthermore, analysis of these key markers in a case control cohort showed significant association to migraine in females at the DXS8043 marker (T1 P = 0.009) and association with MO at DXS8061 (T1 P = 0.05). Further analysis of 11 key genes across these regions showed significant association of a three-marker risk haplotype in the NSDHL gene at Xq28 ( P = 0.0082). The results of this study add further support to the presence of migraine susceptibility loci on chromosome Xq27 and Xq28 as well as point to potential candidate genes in the regions that warrant further investigation.